HOLISTIC APPROACH FOR CHILDHOOD OBESITY THROUGH AYURVEDA –A GROWING HEALTH PROBLEM - Gupta Megha; singh Pankaj; Prof.Verma Mithilesh (International Journal of Applied Ayurved Research, 2019)
Obesity comes with many health hazards and numbers of overweight person are in increasing rapidly worldwide and our country also. Sthoulya is a disease of medovaha srotas and kapha-vata pradana tridoshaj vyadhi. Change in diet and life style, weakens the digestive fire leading to the formation of Aama. The Aama obstructs the srotasas (micro and macro channels), hampers the nourishment of uttarottara dhatu and disrupts the formation of tissues. This increase the medodhatu and cause imbalance in kapha dosha. Aama causes imbalance in naturally flowing vata. Imbalanced vata increases agni leading to increase in appetite and thirst further increasing the medo dhatu. Need is to control overweight along with improvement in general health aspect. There are many Ayurvedic drugs under research for obesity management.